The Textual and Contextual Study of Lengger Banyumasan Dance Performance in Sea Alms Ceremony in Sidanegara Village - Zaharani Salsabila; Joko Wiyoso (Jurnal Seni Tari, 2023)
The lengger Banyumasan performance at the sea alms ceremony in the village of Sidanegara is a folk art that is presented in a ritual culture of the community. These rituals affect textual and contextual values in the lengger dance performance. The purpose of this study was to determine the textual and contextual values in the lengger Banyumasan performance at the sea alms ceremony in the village of Sidanegara. Field data was processed using qualitative research methods and a phenomenological approach. Data collection techniques used are observation, interviews, and documentation. The data validity technique used is the triangulation technique. Data were analyzed using data reduction, presentation, and conclusion stages. The results show that the performance of the lengger Banyumasan dance at the sea alms ceremony has a performance pattern consisting of the lenggeran round which is included in the procession and tasyakuran evening and has a performance function consisting of individual functions that have spiritual values such as supplication, worship, and expression of gratitude to God Almighty, social functions consisting of entertainment and economic functions, as well as association or brotherhood functions. Suggestions from the researchers for artists to maintain cohesiveness to continue to develop and preserve the lengger Banyumasan art form.